Explaining Support for Border Closures During the COVID-19 Pandemic: Exposure, Political Attitudes, or Pandemic Policy Feedback? - Elie Michel; Manatschal, Anita; Eva G T Green (My University, 2024)
The closing of national borders was one of the most far-reaching policy measures adopted to limit the spread of the virus during the coronavirus disease 2019 pandemic. Despite its unprecedented nature and far-reaching impact on individual lives, blocking almost all human movements not only into but also out of states, popular support for this measure was surprisingly high. How can this support be explained? Using an original 4-wave panel dataset across 11 countries together with cross-national policy data, we explore individual and contextual drivers of border closure support throughout 2020. We find that higher support can partly be explained by political attitudes related to cross-border mobility, such as distrust in foreigners or right-wing ideology. Primarily, however, support for closing borders is shaped by respondents’ evaluation of governments’ handling of the pandemic, as well as the intensity and timing of the constraining measures. We also find that support wanes over time, which may indicate a policy fatigue effect. Interestingly, health concerns (exposure to the virus) have almost no influence on support. Even in this exceptional situation, and when confronted with a new policy issue, citizens’ preferences are thus primarily a politically driven response to government measures.